The Relation between Students’ Optimism and Listening Achievement - Fithrah Auliya Ansar; Nunun Indrasari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
Learning is more about the act of transferring knowledge. However, the successfulness of students depends on their emotions in learning knowledge. Optimism is one of the factor that may influence the students’ achievement in the lesson. The purpose of the research is to find the correlation between the optimism and students’ listening achievement through knowing  the way of optimism works in listening class and the significant influence between students optimism and listening achievement. The method of this research is correlation method by using quantitative data. This research was conducted in the class of listening in the third semester of University of Raden Intan Lampung in the academic year 2018-2019. The population of this study is the student of the third semester of listening class of State Islamic University Raden Intan Lampung.  The instruments used in this research are Questionnaire and documentation. The finding in this result is the optimism level of students were mostly moderate. There were 81.8 % of moderate optimism by the students in listening and the result of correlation coefficient value was 0.668 which means that there was a positive correlation between them. As a result, The higher of  the students’ optimism can cause the higher achievement of the students in listening class.